2014
DOI: 10.1021/es502701u
|View full text |Cite
|
Sign up to set email alerts
|

Speciation and Reactivity of Uranium Products Formed during in Situ Bioremediation in a Shallow Alluvial Aquifer

Abstract: In this study, we report the results of in situ U(VI) bioreduction experiments at the Integrated Field Research Challenge site in Rifle, Colorado, USA. Columns filled with sediments were deployed into a groundwater well at the site and, after a period of conditioning with groundwater, were amended with a mixture of groundwater, soluble U(VI), and acetate to stimulate the growth of indigenous microorganisms. Individual reactors were collected as various redox regimes in the column sediments were achieved: (i) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 55 publications
8
69
0
Order By: Relevance
“…Although significant efforts have been made to remediate the site through removal of surface contaminated soils and sediments, persistent low-level uranium concentrations have been detected in the subsurface. Given that previous studies have demonstrated that NRZs are "hot spots" of immobilized uranium within the aquifer (Campbell et al, 2012), the annual intrusion of DO and oxidation of reduced species such as monomeric U 4+ in these regions may at least partly account for the observed persistence of uranium in groundwater Alessi et al, 2014). Indeed, our geochemical measurements showed a sharp spike in U 6+ concentrations during DO intrusion into the NRZ location sampled here (Figure 2).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Although significant efforts have been made to remediate the site through removal of surface contaminated soils and sediments, persistent low-level uranium concentrations have been detected in the subsurface. Given that previous studies have demonstrated that NRZs are "hot spots" of immobilized uranium within the aquifer (Campbell et al, 2012), the annual intrusion of DO and oxidation of reduced species such as monomeric U 4+ in these regions may at least partly account for the observed persistence of uranium in groundwater Alessi et al, 2014). Indeed, our geochemical measurements showed a sharp spike in U 6+ concentrations during DO intrusion into the NRZ location sampled here (Figure 2).…”
Section: Discussionsupporting
confidence: 56%
“…Aqueous uranium increases were also detected across the remaining depths at location BND, and all depths in the NRZ well (Figure 2), although the exact mechanisms for mobilization remain unclear. Two possible mechanisms include (1) DO-dependent re-oxidation of reduced uranium phases in the saturated portion of the aquifer Alessi et al, 2014), and (2) Despite these specific examples of abiotic responses to water table rise and DO intrusion, many geochemical parameters between depths at a specific location were remarkably similar, indicative of (1) greater horizontal rather than vertical heterogeneity across the saturated subsurface (Figure 2), and (2) some level of geochemical stability within a particular well. Despite being separated by only 150 ft., samples from the MID wells exhibited greater geochemical stability than samples from the BND location (Figure 3).…”
Section: Fluctuating River Stage Drives Biogeochemical Shifts In the mentioning
confidence: 99%
“…Such U(IV) mononuclear species could either be sorbed to the surface of phosphate as well as silicate minerals, or be bound to organic phosphoryl groups (Alessi et al, 2014b). The major occurrence of such species in lacustrine sediments has important environmental implications since mononuclear U(IV) species are potentially more labile than uraninite (Cerrato et al, 2013;Alessi et al, 2014a) and polymerised non-crystalline U(IV) phosphate phases (Alessi et al, 2014b). Such lability raises issues concerning the long term fate of the mononuclear U(IV) species, especially when subjected to sharp redox changes, for example in sediment remediation strategies as dredging operations.…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…In natural anoxic environments such as estuarine and coastal sediments, early diagenesis conditions favour the reduction of U(VI) species into low solubility U(IV) species, which decreases uranium concentrations in overlying waters and sediment pore-waters (Barnes and Cochran, 1993). Researchers addressing remediation of U-contaminated groundwaters have focused on in situ biostimulation strategies involving microbial reduction of U(VI) (Wu et al, 2007;Yabusaki et al, 2007) into biogenic uraninite (Suzuki et al, 2005;Bargar et al, 2008) as well as non-uraninite U(IV) phases (Kelly et al, 2008;Bargar et al, 2013;Alessi et al, 2014a;Newsome et al, 2014). Ex situ incubations of aquifer sediments under anoxic conditions have highlighted the importance of non-crystalline U(IV) species as major products of microbial reduction of U(VI) (Sharp et al, 2011;Alessi et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Insoluble U(IV) can precipitate as the simple mineral uraninite, UO 2 , but more often forms minerals with calcium and phosphates such as autunite [119]. A more labile precipitate has also been identified known as monomeric U(IV) [120] [121].…”
Section: Factors Influencing Reduction Reaction Rates and Electron Flowmentioning
confidence: 99%